Variasi Tingkat Keasaman Dalam Ekstraksi Pektin Kulit Buah Durian - Gunawan Ardiansyah; Faizah Hamzah; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to obtain the best pH in the extraction of durian rind pectin. Research conducted experiments using a completely randomized design (CRD) with four treatments are: P1 (extraction pH 1.5); P2 (extraction pH 2.0); P3 (extraction pH 2.5), and P4 (extraction pH 3.0). The results showed that the variation in the level of acidity in the manufacture of durian rind pectin significant effect on yield, methoxyl content, moisture content, ash content and organoleptic assessment of the color. Pectin P1-P4 treatment meets the standards IPPA (International Pectin Producers Association) For The best treatment in this study is the P1 treatment (extraction pH 1.5) produced pectinbetter to yield 2.60%, 4.35% methoxyl content, water content 8.38%, ash content 7.69% and pectin brown color.   Keywords: pectin, durian skin, and acidity (pH)